Improving Early Estimates of Large Earthquake's Final Fault Lengths and Magnitudes Leveraging Source Fault Structural Maturity Information. Issue 14 (13th July 2020) - Hutchison, Allie A.; Böse, Maren; Manighetti, Isabelle
Abstract: Earthquake early warning would be improved if the final size of an ongoing earthquake could be predicted early in the rupture process. Previous research relies largely on parameters derived from seismic waveforms, resulting in widely varied estimates of how much of the rupture must be complete before final sizes can be predicted. We demonstrate here that incorporating prior information on along‐strike variation in source fault structural maturity helps improve constraints on the earthquake's final size. Using surface slip profiles from 26 large continental earthquakes worldwide, we derive a generic empirical relation between earthquake slip, rupture length, and along‐strike variability in source fault maturity. Using this equation, we fit successive slip profiles developing during each earthquake and find that, on average, we predict the final length and magnitude of an earthquake once it has reached ~20% of its total length. Our findings thus demonstrate a clear determinism in the rupture process. Plain Language Summary: When an earthquake initiates, an important question is whether and when we can anticipate what its final size will be. Previous studies have searched the answer to this question in seismic data from the earthquake alone. Here we suggest that we should incorporate additional information on the tectonic source fault that is rupturing. Based on earthquake slip‐length functions measured at the ground surface, we develop a generic empirical equation between earthquake slip, rupture length, and along‐strike changes in source fault structural maturity, for continental earthquakes. We show that applying this relationship to evolving earthquake slip profiles improves how quickly earthquake length and magnitude can be determined. These findings demonstrate that part of the rupture process is controlled by the physical properties of the source faults and may have important implications for earthquake early warning. Key Points: We parameterize a generic relationship between along‐strike fault maturity, coseismic slip, and final rupture length Using fault maturity as a prior improves earthquake magnitude and rupture length predictions as needed for earthquake early warning We predict final length and magnitude once earthquake rupture has reached ~20% of its total length, what shows a clear determinism in the rupture process